2017
DOI: 10.4103/joc.joc_209_16
|View full text |Cite
|
Sign up to set email alerts
|

Histological follow-up in patients with atypical glandular cells on Pap smears

Abstract: Context:Atypical glandular cells (AGCs) result in the Papanicolaou (Pap) smear may be associated with significant genital and nongenital neoplastic processes.Aims:To evaluate the underlying histopathology in women who had AGCs on Pap smears.Settings and Design:Retrospective cross-sectional study.Patients and Methods:Clinicopathological data of patients who had AGC on Pap smears and underwent histological workup between January 2004 and December 2014 were retrieved from the computerized database of a tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
(35 reference statements)
6
10
0
Order By: Relevance
“…Although several studies have investigated the incidence, cytopathological findings, and malignancy ratio of AGC, the results vary significantly. The incidence of AGC ranges from 0.08% to 2.1% in the literature 3‐9 . Similar to what is reported in the literature, the incidence rate of AGC was 0.22% in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although several studies have investigated the incidence, cytopathological findings, and malignancy ratio of AGC, the results vary significantly. The incidence of AGC ranges from 0.08% to 2.1% in the literature 3‐9 . Similar to what is reported in the literature, the incidence rate of AGC was 0.22% in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In the literature, clinically significant pathologies were reported to range widely from 15% to 59% of women with AGC Pap results 4,5,7‐15 . The malignancy rate in AGC‐FN cases was higher than that in AGC‐NOS cases 8,10,16,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive recent work reviewed multiple aspects on the detection of uterine glandular lesions by SurePath in a Bethesda reporting environment [21], while other available SurePath cytology-histology correlation studies offer important considerations. However, they focus on a specified aspect of performance (detection rate in endometrial carcinomas [22]), use a mixed ThinPrep-SurePath pool of cases without comparison between the two technologies [23], or report cytology findings in a non-Bethesda reporting environment, making the findings less applicable to laboratories adhering to Bethesda guidelines [24-26]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that subcategorization of AGUS may give a higher yield of significant lesions in specific subgroups [11,[13][14][15] We can assume that the risk of an underlying malignant or premalignant lesion is of the same magnitude in Norway, and our current practice of follow up is justified and in compliance with international studies [10,13,15].…”
Section: Introductionmentioning
confidence: 93%